Multimedia Authoring for Communities of Teachers - Guerraz, Agnès and Roisin, Cécile and Mikác, Jan and Deltour, Romain (International Journal of Web-Based Learning and Teaching Technologies, 2007)
One way of providing technological support for communities of teachers is to help participants to produce, structure and share information. As this information becomes more and more multimedia in nature, the challenge is to build multimedia authoring and publishing tools that meet requirements of the community. In this paper, we analyze these requirements and propose a multimedia authoring model and a generic platform on which specific community-oriented authoring tools can be realized. The main idea is to provide template-based authoring tools while keeping rich composition capabilities and smooth adaptability. It is based on a componentoriented approach integrating homogeneously logical, time and spatial structures. Templates are defined as constraints on these structures.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9qd2x0dC4yMDA3MDcwMTAx